ROLE OF AQUATIC PLANTS IN INCREASE OF FISH PRODUCTIVITY IN DENGIZKOL LAKE (Conferencea, 2022)
The article describes the role of aquatic plants and their importance in increasing fish productivity in Lake Dengizkol. Information is provided on the biotechnological propagation of aquatic plants rich in biologically active substances and their use as feed for Ctenopharyngodon idella.